A non‐contact vision‐based system for multipoint displacement monitoring in a cable‐stayed footbridge. Issue 5 (13th February 2018) - Xu, Yan; Brownjohn, James; Kong, Dali
Summary: Vision‐based monitoring receives increased attention for measuring displacements of civil infrastructure such as towers and bridges. Currently, most field applications rely on artificial targets for video processing convenience, leading to high installation effort and focus on only single‐point displacement measurement, for example, at mid‐span of a bridge. This study proposes a low‐cost and non‐contact vision‐based system for multipoint displacement measurement based on a consumer‐grade camera for video acquisition and a custom‐developed package for video processing. The system has been validated on a cable‐stayed footbridge for deck deformation and cable vibration measurement under pedestrian loading. The analysis results indicate that the system provides valuable information about bridge deformation of the order of a few centimetres induced, in this application, by pedestrian passing. The measured data enable accurate estimation of modal frequencies of either the bridge deck or the bridge cables and could be used to investigate variations of modal frequencies under varying pedestrian loads.